2020
DOI: 10.1002/jac5.1369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of discharge education by clinical pharmacists on patients' adherence to post‐percutaneous coronary intervention medications: A retrospective cohort study using real‐world data

Abstract: BackgroundSecondary prevention post myocardial infarction by optimizing secondary prevention cardiovascular medications is important; however, adherence to these medications is essential to achieve benefits. Nevertheless, the impact of education provided by clinical pharmacists to patients post primary percutaneous coronary intervention (PCI) has not yet been evaluated in a real‐world context.MethodsThis retrospective observational cohort study aimed to assess the impact of education provided by clinical pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…(2016) used to teach male adolescents about smoking prevention. In contrast, sessions designed for adult participants were based on didactic lecturing and discussions ( Bakarman et al ., 2019 ; Rahhal et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2016) used to teach male adolescents about smoking prevention. In contrast, sessions designed for adult participants were based on didactic lecturing and discussions ( Bakarman et al ., 2019 ; Rahhal et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that patient compliance with the comorbidity regimen is a valued parameter in improving the effectiveness of health literacy programs. In the study by Rahhal et al , (2021) , investigators assessed compliance with the regimen of adult patients ( n = 1334) who underwent percutaneous coronary intervention (PCI) and received clinical pharmacists’ educational interventions during discharge from the hospital. These investigators found significant adherence to post-PCI medication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation